2020
DOI: 10.21203/rs.3.rs-47415/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Distal Tibial Tuberosity High Tibial Osteotomy on Postoperative Patellar Height and Patellofemoral Joint Degeneration

Abstract: Background: Distal tibial tuberosity high tibial osteotomy (DTT-HTO) can prevent distalization of the tibial tuberosity and thus patella infra. However, no studies on the clinical and radiological effects of DTT-HTO on the patellofemoral joint have been conducted. The purpose of the study was to evaluate the effect of DTT-HTO on patella height and patellofemoral joint congruity based on the severity of patellofemoral joint OA.Methods: Twenty-nine patients (33 knees) who underwent DTT-HTO and second-look arthro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Open‐wedge distal tibial tuberosity osteotomy has been drawing attention as a valuable surgical option for osteoarthritis with varus knee, especially for patients with patella infra or patellofemoral joint degeneration 4,5,15,16 . Its difference from OWHTO is the descending osteotomy at the tibial tuberosity.…”
Section: Discussionmentioning
confidence: 99%
“…Open‐wedge distal tibial tuberosity osteotomy has been drawing attention as a valuable surgical option for osteoarthritis with varus knee, especially for patients with patella infra or patellofemoral joint degeneration 4,5,15,16 . Its difference from OWHTO is the descending osteotomy at the tibial tuberosity.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that a surgically induced decrease in patella height might result in anterior knee pain, patellofemoral arthrosis, and decreased range of motion [38][39][40] . Subsequent patellofemoral biomechanical modifications were also demonstrated in previous studies with the development of patella or trochlear OA in 41% of patients who underwent OWHTO 17,41 .…”
Section: Functional Outcome Of the Patellofemoral Jointmentioning
confidence: 99%
“…1). Several clinical studies have reported clinical advantages of MOWDTO over conventional MOWHTO [21][22][23]; however, there is concern of increased bleeding from the bone marrow compared to MOWHTO due to the triplane osteotomy technique which requires three osteotomy surface areas. To the best of our knowledge, there has been no randomized controlled trials that investigated the effectiveness of TXA administration in MOWDTO.…”
Section: Introductionmentioning
confidence: 99%